(3GdeNJGQ ef JQSjd GdbGVj GdaGVd(B/ (3Ch ef JQSd GdbGVj GdaGVds - (3eLghds
(3ChdgG (B:s
(3hHYO, agPG GdeNJGQ ef JQSjd GdbGVj hRjQ Gdedc GdfGUQ UdGM GdOjf cJH Edi GdOjhGf GdYRjR HHZOGO aj SfI SHY hKeGfjf hNeSI eFg s
(3BNQgG (B:s
(3MJi Cfg CgOQ HUGMH UbdjI hCHGWjdg GdJj jQOO PcQgG hde jNa CeQgG hGddg JYGdi CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B22 s
Keywords: (3GdCOHs